Development Of Interactive Digital Media To Improve Early Childhood Reading Skills - Cut Ayu Nazila; Rahma Rahma; Salpina Salpina (Universitas Muhammadiyah Surakarta, 2026)
Early reading skills are an important part of early childhood literacy development that needs to be optimally stimulated. However, the learning process in kindergarten still uses many conventional methods, so the development of children's early reading skills is not optimal. This interactive Digital Media has the potential to attract children's attention, provide an immersive learning experience, and create a participatory atmosphere. The research method used is Research and Development (RND) with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The data collection technique was carried out through observation, and a questionnaire to assess the child's initial reading ability on the Likert scale. The results of the study show that the interactive digital media developed is in the category of very feasible based on expert assessment and teacher response. In addition, the use of interactive digital media is able to improve children's early reading skills, especially in the aspects of letter recognition, reading syllables, and reading simple words. The implications of this study show that interactive digital media can be an effective alternative learning media in supporting the development of early childhood literacy.